1984
DOI: 10.1177/1077727x8401200403
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Home Economics Researchers

Abstract: This study describes researchers in home economics and characteristics associ ated with their research productivity using data from the 1979 AHEA survey. The 737 researchers were all of the 16,894 respondents who reported research was a major function in their employment and who were employed full‐time for 9 to 12 months. The researchers included 7.3 percent males. Based on the modes, the researchers are characterized as having doctoral degrees, being in the home economics education area of home economics, bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
1
0
2
Order By: Relevance
“…He did not blame age for it rather increasing administrative duties cause low research productivity among senior faculty members. Kotrlik et al (2002) agreed with them whereas ssome other researchers found positive relationship between age and research productivity (Blackburn et al, 1991;Gorman & Scruggs, 1984;Pfeffer & Langton, 1993;Vasil, 1992). With reference to experience, Pfeffer and Langton (1993) testified that it was significantly correlated with total number of research publications but not with recent ones.…”
Section: Discussionmentioning
confidence: 62%
“…He did not blame age for it rather increasing administrative duties cause low research productivity among senior faculty members. Kotrlik et al (2002) agreed with them whereas ssome other researchers found positive relationship between age and research productivity (Blackburn et al, 1991;Gorman & Scruggs, 1984;Pfeffer & Langton, 1993;Vasil, 1992). With reference to experience, Pfeffer and Langton (1993) testified that it was significantly correlated with total number of research publications but not with recent ones.…”
Section: Discussionmentioning
confidence: 62%
“…Συνεπώς, αν αναλογιστούμε ότι οι επιστημόνισσες υπερ-συγκεντρώνονται και συνωθούνται στις Θεωρητικές Επιστήμες, αναμένεται να επιδεικνύουν διαφορετικού μεγέθους συνολική ερευνητική δραστηριότητα (Nakhaie, 2002: 3) Gorman et al, (1984), Radhakrishna et al (1994), Kyvik et al, (1994) και , οι οποίοι υποστήριξαν ότι η συμμετοχή στην έρευνα των πτυχιούχων φοιτητών/-τριών συσχετίζεται με το ερευνητικό και συγγραφικό έργο του επιστημονικού προσωπικού, εύρημα που επιβεβαιώνει τα συμπεράσματα και παλαιότερων ερευνών (βλ. Berelson: 1960, Hagstrom: 1965.…”
Section: ποσοτικές μέθοδοιunclassified
“…εξέλιξη, συνταξιοδότηση) επηρεάζουν τα επίπεδα κινήτρων κάποιου Ramsden (1994). διαπίστωσε ότι η ηλικία δε συσχετίζεται με την ερευνητική παραγωγή, σε αντίθεση με τουςBlackburn et al (1991), καθώς καιGorman and Scruggs (1984). ΟιKotrlik et al (2001), βασιζόμενοι σε μια έρευνα επί 228 μελών διδακτικού προσωπικού Γεωπονικών Σχολών στις ΗΠΑ, κατέληξαν στο συμπέρασμα ότι η ηλικία δεν επηρεάζει σημαντικά την ερευνητική παραγωγή, ενώ η Williams et al (2001) διαπίστωσε ανάλογα αποτελέσματα στα Τμήματα του Πανεπιστημίου Ανάπτυξης Ανθρωπίνων Πόρων.Άλλες προσπάθειες να διερευνηθούν οι παράγοντες που επηρεάζουν το ερευνητικό συγγραφικό έργο των επιστημόνων, επιχειρούν να προσδιορίσουν ποια στους υπερ-δραστήριους και πολυγραφότατους ερευνητές.…”
unclassified